War, government and power in late medieval France - Allmand, C. T. (Liverpool University Press, 2000)
The essays in this volume portray the public life of late medieval France as that country established its position as a leader of western European society in the early modern world. A central theme is the contribution made by contemporary writers, chroniclers and commentators, such as Jean Froissart, William Worcester and Philippe de Commynes, to our understanding of the past. Who were they? What picture of their times did they present? Were their works intended to influence their contemporaries and what success did they enjoy? Other contributions deal with the exercise of political power, the.